Beyond empty plates: Impact of food insecurity on early childhood development - Rishika Satheesh (Undergraduate Research Journal for the Human Sciences, 2025)
Food insecurity impacts millions of children worldwide, including 2.5 million children in the UK who lack consistent access to nutritious food. This paper investigates the detrimental effects of food insecurity on early childhood development, focusing on physical, cognitive and behavioural development. The first 1000 days are critical for child’s brain and body development, therefore nutritional deficiencies during this period can lead to stunted growth, weakened immunity and cognitive impairment such as poor memory due to low iron levels. Furthermore, food insecurity is associated with behavioural changes in children such as externalizing behaviours like aggression and internalizing behaviours like anxiety. This paper highlights the need for thorough strategies, including government policies, community level initiatives and educational programs for parents to address and increase awareness about food insecurity. By incorporating these interventions to improve food accessibility, these measures can support the developmental requirements of at-risk children. Further research is suggested to develop targeted solutions, to avoid lasting impacts on health and development in children.
Keywords: Food insecurity; Nutritional Deficiency; Cognitive impairment; Child health; Parental Education.